2009
DOI: 10.1371/journal.pone.0005976
|View full text |Cite
|
Sign up to set email alerts
|

Plk1-Dependent Recruitment of γ-Tubulin Complexes to Mitotic Centrosomes Involves Multiple PCM Components

Abstract: The nucleation of microtubules requires protein complexes containing γ-tubulin, which are present in the cytoplasm and associate with the centrosome and with the mitotic spindle. We have previously shown that these interactions require the γ-tubulin targeting factor GCP-WD/NEDD1, which has an essential role in spindle formation. The recruitment of additional γ-tubulin to the centrosomes occurs during centrosome maturation at the G2/M transition and is regulated by the mitotic kinase Plk1. However, the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
229
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(246 citation statements)
references
References 37 publications
(75 reference statements)
14
229
3
Order By: Relevance
“…It was also localized at the midbody in telophase in HeLa cells [7]. Haren et al found that recruitment of γ-tubulin and AURKA (Aurora Kinase A) to the mitotic centrosome were Plk1 dependent before spindle formation in HeLa cells [22]. Petronczki et al also found that Plk1 was localized to the centromere at the metaphase stage and involved in the stability of spindle assembly checkpoint (SAC)-dependent kinetochore-microtubule interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It was also localized at the midbody in telophase in HeLa cells [7]. Haren et al found that recruitment of γ-tubulin and AURKA (Aurora Kinase A) to the mitotic centrosome were Plk1 dependent before spindle formation in HeLa cells [22]. Petronczki et al also found that Plk1 was localized to the centromere at the metaphase stage and involved in the stability of spindle assembly checkpoint (SAC)-dependent kinetochore-microtubule interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Spd-2 mutant flies have reduced CNN and gtubulin in several cell types (Dix and Raff 2007;Giansanti et al 2008), and injection of antibodies against Spd-2 into Drosophila embryos prevents CNN recruitment in the vicinity of the centriole ). CDKRAP2 and Cep192, human counterparts of CNN and Spd-2, also increase on centrosome maturation as does pericentrin, and the proteins show interdependency for the recruitment of g-tubulin (Haren et al 2009;Lee and Rhee 2011). In part, this reflects the physical association of g-tubulin with the amino-terminal part, and pericentrin with the carboxy-terminal part of CDKRAP2 (Fong et al 2008;Choi et al 2010;Wang et al 2010).…”
Section: Pcm Assemblymentioning
confidence: 99%
“…Polo kinase or Plk1 (Polo-like kinase 1) is the major kinase required for the dramatic increase of PCM that occurs before mitotic entry (Blagden and Glover 2003;Glover 2005). Its kinase activity is needed for the normal localization of Spd-2/Cep192, CNN/CDK5RAP2, pericentrin, and Nedd1 (Haren et al 2009;Zhang et al 2009;Hatch et al 2010;Lee and Rhee 2011;Fu and Glover 2012). Interestingly, Drosophila Polo is restricted to zone II (i.e., the vicinity of the microtubule wall).…”
Section: Pcm Assemblymentioning
confidence: 99%
“…43 Nevertheless, Plk1 activity slowly rises from S through G2 and peaks in mitosis. Plk1 not only mediates centriole maturation 42,44,45 but also primes centrioles for disengagement 34 by phosphorylating cohesin and accelerating its cleavage by separase. 46 In addition, Plk1 may regulate centrosomal localization of shugoshin and mediate centriole disengagement by modifying shugoshin's activity in preserving centriole cohesion.…”
Section: Excess Baggage: How Cancer Cells Acquire Extra Centrosomesmentioning
confidence: 99%